Hagar Perempuan Merdeka: Inspirasi bagi Perjuangan Kesetaraan Gender - Mamus, Martina (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2017)
Everyone longs for an emancipated life as children of God. Everybody hopes for a life without discrimination, oppression and suppression. People have talents to support their lives. Hagar, a biblical figure, is a model of a woman who owns the talents. Hagar, the slave of Sarah, tried hard to overcome the violence and oppression in her life, and she succeeded. Her personality could be a model for many women trying to defend their rights and dignities, especially in Asia. Hagar sets an example of defending the marginalised. Her struggle becomes an instrument to achieve the equality and the harmony of life for both men and women. Hagar is an inspiration, as she strongly believes in God who saves and frees her. She had the courage to escape from his master’s loyalty and hence she was independent: she did not give up amid the many difficulties she faced as a single parent. The author is convinced that only when men and women work and walk together in one heart and mind to create a more dignified humanity as willed by God, will this kind of struggle succeed.